THE IMAGE OF THE ‘OTHER’ IN "SNAKE WIND" AND "AEGEANS" (Journal of Contemporary Philology, 2018)
Literary science and comparative  literature have  developed imagology as a  separate disciplinedealing with the study of the images of the Other. The most common form of an image of the Other is the stereotype a term that has found broad use in all social theories  during  recent  decades. The  stereotype  becomes  a  means  for  recognition, labeling, orientation, validation and evaluation. In the history of studying stereotypes, ethnical and cultural stereotypes have received the greatest amount of attention. In our cultural  and  literary  history,  a  special  place  is  reserved  for  the  stereotypes  of Macedonian victims exiled during the Civil War in Greece. In time, and throughout time,  the  Aegeans  and  “Aegeanism”  in  general  have  received  certain  ideological contents,  transforming  them  into  a  myth  which  can  have  either  positive or  negative uses depending on the  context.  The  positive  interpretation  of that  myth can be  seen through the preferential treatment of so-called Aegean themes found in the works of renowned artists coming from that part of Macedonia. The negative interpretation can be seen in the factuality of the negative consequences against Aegeans stemming from negative stereotypes about them, such as their alleged unsuitability to do public work, or viewing them as suspicious in certain political contexts.
Keywords: images; stereotypes; otherness; culture; history